Possibility of reconstruction of dental plaster cast from 3D digital study models - Kašparová, Magdaléna; Gráfová, Lucie; Dvorak, Petr; Dostálová, Taťjana; Procházka, Aleš; Eliášová, Hana; Prusa, Josef; Kakawand, Soroush (Biomedical engineering online, 2013)
OBJECTIVES: To compare traditional plaster casts, digital models and 3D printed copies of dental plaster casts based on various criteria. To determine whether 3D printed copies obtained using open source system RepRap can replace traditional plaster casts in dental practice. To compare and contrast the qualities of two possible 3D printing options--source system RepRap and commercially available 3D printing. DESIGN AND SETTINGS: A method comparison study on 10 dental plaster casts from the Orthodontic department, Department of Stomatology, 2nd medical Faulty, Charles University Prague, Czech Republic. MATERIAL AND METHODS: Each of 10 plaster casts were scanned by inEos Blue scanner and the printed on 3D printer RepRap [10 models] and ProJet HD3000 3D printer [1 model]. Linear measurements between selected points on the dental arches of upper and lower jaws on plaster casts and its 3D copy were recorded and statistically analyzed. RESULTS: 3D printed copies have many advantages over traditional plaster casts. The precision and accuracy of the RepRap 3D printed copies of plaster casts were confirmed based on the statistical analysis. Although the commercially available 3D printing enables to print more details than the RepRap system, it is expensive and for the purpose of clinical use can be replaced by the cheaper prints obtained from RepRap printed copies. CONCLUSIONS: Scanning of the traditional plaster casts to obtain a digital model offers a pragmatic approach. The scans can subsequently be used as a template to print the plaster casts as required. Using 3D printers can replace traditional plaster casts primarily due to their accuracy and price.
Keywords: Printing; sádrové obvazy; Models, Anatomic; tiskařství; anatomické modely; zubní lékařství; Casts, Surgical; Dentistry